2022
DOI: 10.30935/conmaths/12382
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Conceptual Difficulties in Teaching Senior High School Organic Chemistry

Abstract: Teachers are one of the important factors influencing students' learning of chemistry as they (teachers) transform the content for students. When teachers do not have a sound scientific understanding of the chemistry behind the organic concepts considered to be difficult, they are likely, not able to transform sound scientific understanding for their students. Hence, the need to examine the conceptual difficulties of teachers in teaching organic chemistry to senior high school students. Teachers, teaching chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Most research came to the conclusion that instructors' selected methods of instruction were mostly the reason for the poor performance of students [1]. Based on the findings of the research, most chemistry students receive instructions through inefficient methods, while some succeed on exams despite having severe misconceptions about certain chemical reactions [7][8][9][10]. The traditional method of instruction that is frequently used to teach chemistry has not been able to meet the needs of contemporary students.…”
Section: Introductionmentioning
confidence: 99%
“…Most research came to the conclusion that instructors' selected methods of instruction were mostly the reason for the poor performance of students [1]. Based on the findings of the research, most chemistry students receive instructions through inefficient methods, while some succeed on exams despite having severe misconceptions about certain chemical reactions [7][8][9][10]. The traditional method of instruction that is frequently used to teach chemistry has not been able to meet the needs of contemporary students.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed students' difficulties in organic chemistry concepts (Adu-Gyamfi & Asaki, 2022, 2023Adu-Gyamfi et al, 2013Bhattacharyya & Bodner, 2005;Childs & Sheehan, 2009;Ferguson & Bodner, 2008;Graulich, 2015;Wasacz, 2010). However, very few focused on OQA concept (Adu-Gyamfi & Anim-Eduful, 2022;Anim-Eduful & Adu-Gyamfi, 2021, 2022a, 2022b in organic chemistry.…”
Section: Introductionmentioning
confidence: 99%